Management of single complete dentures in parkinson’s patients - Rafael Hendarto; Muslita Indrasari (Indonesia Prosthodontic Association, 2025)
Background: Parkinson's disease is a progressive neurodegenerative disorder that disrupts control of body movement, which directly affects oral function, including adaptation to dentures. Motor symptoms such as tremors, bradykinesia, and rigidity, as well as non-motor manifestations such as cognitive impairment and depression, pose challenges in prosthodontic rehabilitation. Purpose: Prosthodontic management of single complete denture for an elderly patient with advanced stage Parkinson's disease, highlighting clinical challenges, care strategies, and the role of caregivers. Case: A 75-year-old female with diagnosis of Braak stage 6 Parkinson's disease have difficulty chewing due to complete tooth loss in the upper jaw and nearly total tooth loss in the lower jaw. The patient experienced motor limitations, medication-induced xerostomia, and difficulty understanding instructions. Management: Prosthodontic treatment consisted of fabricating conventional single complete dentures made of acrylic on the upper and lower jaws. Management of these limitations involved an individualized approach, simple denture design, modification of the tooth arrangement, and comprehensive education involving caregivers, this includes training in denture wearing and salivary gland massage to address lacks of saliva. Conclusion: Prosthodontic management in Parkinson's patients requires simple denture design, empathetic, as well as effective communication and education with both the patient and caregiver to achieve optimal oral rehabilitation. This can improve chewing function, comfort, and quality of life for patients. Keywords: Parkinson’s disease, single complete denture, motor Impairment.